2021
DOI: 10.1084/jem.20210582
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic profiling reveals widespread dysregulation of innate immunity and hematopoiesis in COVID-19

Abstract: Our understanding of protective versus pathological immune responses to SARS-CoV-2, the virus that causes coronavirus disease 2019 (COVID-19), is limited by inadequate profiling of patients at the extremes of the disease severity spectrum. Here, we performed multi-omic single-cell immune profiling of 64 COVID-19 patients across the full range of disease severity, from outpatients with mild disease to fatal cases. Our transcriptomic, epigenomic, and proteomic analyses revealed widespread dysfunction of peripher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(187 citation statements)
references
References 145 publications
(232 reference statements)
10
153
1
Order By: Relevance
“…Such NDNs have been already described in cancer patients ( 40 , 79 ) and patients with severe COVID–19, where the presence of dysfunctional neutrophils, including LDNs, was linked to emergency myelopoiesis ( 35 ). Several studies have identified emergency myelopoiesis as a hallmark of fatal COVID–19 ( 42 , 80 ) and particularly neutrophil counts were found to be significantly elevated in patients with COVID–19 and correlated with disease severity ( 81 , 82 ). In this context, it is worth mentioning that in differential analysis, both LDNs/MN–MDSCs and NDNs are counted as peripheral blood neutrophils, affecting the neutrophil–to–lymphocyte ratio in COVID–19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Such NDNs have been already described in cancer patients ( 40 , 79 ) and patients with severe COVID–19, where the presence of dysfunctional neutrophils, including LDNs, was linked to emergency myelopoiesis ( 35 ). Several studies have identified emergency myelopoiesis as a hallmark of fatal COVID–19 ( 42 , 80 ) and particularly neutrophil counts were found to be significantly elevated in patients with COVID–19 and correlated with disease severity ( 81 , 82 ). In this context, it is worth mentioning that in differential analysis, both LDNs/MN–MDSCs and NDNs are counted as peripheral blood neutrophils, affecting the neutrophil–to–lymphocyte ratio in COVID–19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…PG active neutrophils were distinguished by preferential splicing of PTGS2/COX2 (as well as expression for prostaglandin transport LST1) and included a subset that expressed high levels of IL1β decoy receptor IL1R2 33 . Lastly, IL7R + neutrophils (a small but distinct subset that maybe of thymic origin 60 expressed high levels of ribosomal subunit genes (e.g.…”
Section: Immunocytochemistry and Immunohistochemistrymentioning
confidence: 99%
“…Comparing scRNA-Seq findings with published datasets. To test whether dexamethasone-suppressed neutrophil genes at t1 and t2 (Extended Data Table 4) predicted COVID-19 mortality, we repurposed methods described in 33 and employed whole blood bulk RNA-Seq datasets generated by 34 as a validation cohort of 103 samples (where 17 were fatal). Briefly, each of the 103 samples were scored by the aggregated expression of dexamethasone-suppressed neutrophil consensus genes at t1 and t2 using Seurat's AddModuleScore().…”
Section: Statistical Approach For Comparing Cell Proportionsmentioning
confidence: 99%
See 2 more Smart Citations